Women's entrepreneurship in Saudi Arabia: Feminist solidarity and political activism in disguise?. Issue 3 (17th March 2021) - Alkhaled, Sophie
Abstract: This paper is a longitudinal study that uses insights from postcolonial feminism to explore women's entrepreneurship as a political form of feminist organizing for social change in Saudi Arabia. Postcolonial feminist approaches challenge Western feminism, which can obscure the diversity of women's lived experiences, agency, and activism. Through Bayat's (2013) theory of "quiet encroachment, " I identify the ways in which contemporary Western conceptualizations of feminist solidarity and social movements have dismissed "Other" women's "silent, " protracted and (dis)organized activism in parts of the Middle East. By exploring how Saudi women have utilized their entrepreneurial space as a legitimate platform for change, I aim to enrich understanding of women's activism through everyday solidarity practices, which allow them to quietly encroach onto the previously forbidden political space. The findings exemplify how their activism "quietly" developed over time through a three‐step process—from the entrepreneur aiming to empower women within their organization, to developing feminist consciousness within their entrepreneurial network, to becoming a "political activist" lobbying for policy changes for women. These solidarity practices exemplify the West's relationship with "the Other, " and reveal that feminist organizing for social change must be explored within its own context in order to fully appreciate its global political potential.